Severe meningococcal serogroup W sepsis presenting as myocarditis: A case report and review of literature. (May 2019) - Aung, Myat; Raith, Eamon; Williams, Eloise; Burrell, Aidan JC
The global incidence of invasive meningococcal disease due to serogroup W (MenW) has risen over the last decade. The following case emphasises the atypical features of MenW meningococcaemia, which included myocarditis, a rare but important complication. It also highlights the potential novel role that cardiac magnetic resonance imaging can provide in the diagnosis of MenW myocarditis. Complications of these infections can be avoided with early recognition and susceptibility testing to prevent the use of inappropriate antibiotics and treatment failure.